Antifungal Activity of Red Galangal Oil (Alpinia purpurata K. SCHUM) Against Malassezia furfur - Hernandi Sujono; Senadi Budiman; Yusi Fudiesta; Ahmad Sahroni; Jasmansyah Jasmansyah; Lela Lailatul Khumaisah (Jurnal Kartika Kimia, 2019)
Plant red galangal (Alpinia purpurata K. Schum) is one of the many spices used as bio-pharmacy products which contain essential oil that is active as an antifungal and antibacterial agent. Isolation of volatile oil from red galangal rhizome (Alpinia purpurata K. Schum) uses the method of water and steam distillation so as to get the rendemen 0.1062%, the density 0.9524 g/mL and the index of refraction by 1.4862. Results from GC-MS (Gas Chromatography-Mass Spectrometry) retrieved 30 compounds contained in red galangal rhizome oil with 10 major compounds i.e. 1,8-cineole (40.92%), acetyl chavicol (10.33%), cis β-farnesene (6.91%), 1-caryophillene (6.32%), 1-β-bisabolene (3.37%), β-elemene (3.23%), α-pinene (3.20%), β-sesquiphellandrene (2.32%), β-pinene (2.21%), and germacrene-D (1.90%). The inhibition test was done by agar diffusion method and different variations of concentration (1, 2, 3 and 4%) compared with ketoconazole 2% as positive controls and dimethyl sulfoxide (DMSO) as negative controls with an incubation period of 2x24 hours. The test results show that the essential oil of red galangal rhizome (Alpinia purpurata K. Schum) can inhibit the growth of the fungus Malassezia furfur with the inhibitory power on concentrations1, 2, 3 and 4% were 7.15 mm, 13.87 mm, 16.05 mm and 20.05 mm, respectively. As for comparison, ketoconazole 2% was used as positive (+) control that produces inhibitory zone 27.20 mm and dimethyl sulfoxide (DMSO) as negative control (-) which does not produce inhibitory zones. Keywords: Essential oil, red galangal rhizome (Alpinia purpurata K. Schum), Malassezia furfur